2013
DOI: 10.1007/s00701-013-1877-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors affecting graft infection after cranioplasty

Abstract: The results of this study suggest that long operative times (> 120 min), craniectomy with temporalis muscle resection, the presence of preoperative subgaleal fluid collection, and postoperative wound disruption may be risk factors for graft infection after cranioplasty. Surgical techniques should be developed to reduce operative time and to avoid temporalis muscle resection when possible. In addition, meticulous dural closure aimed at reducing the formation of subgaleal fluid collection is important for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 16 publications
4
32
1
3
Order By: Relevance
“…We found no significant association of age, sex, DM, and mechanism of injury (SAH, trauma, ischemic stroke) with postcranioplasty infection, which is consistent with the published literature. 22,29 Reoperation for hematoma showed no significant effect in our study, even though the need for multiple procedures has been shown to increase the risk of cranioplasty site infection. 29,43,47 On the other hand, Cheng et al's work 9 showed that the number of procedures does not affect the risk of graft infection following cranioplasty.…”
Section: Timing Infection and Hydrocephaluscontrasting
confidence: 61%
“…We found no significant association of age, sex, DM, and mechanism of injury (SAH, trauma, ischemic stroke) with postcranioplasty infection, which is consistent with the published literature. 22,29 Reoperation for hematoma showed no significant effect in our study, even though the need for multiple procedures has been shown to increase the risk of cranioplasty site infection. 29,43,47 On the other hand, Cheng et al's work 9 showed that the number of procedures does not affect the risk of graft infection following cranioplasty.…”
Section: Timing Infection and Hydrocephaluscontrasting
confidence: 61%
“…Although autografting, that is, either reimplantation of the excised bone flap [6,7], or transfer of cortical, cancellous or corticocancellous bone from any anatomic site to the defect site in the same subject, is obviously the best choice owing to the lack of immune or foreign body reactions, absence of a risk of transmission of disease, and the potential of the graft to be incorporated as biologically active and dynamic living tissue it has certain inherent limitations and disadvantages. Bone flap/graft resorption and infection [8,9], donor site morbidity, inadequate quantity of graft harvestable to bridge large cranial defects, prolonged intra-operative time, intraoperative blood loss and requirement of transfusions, need for surgical expertise and delayed post operative recovery [10] are definite drawbacks of autografting. Advanced age, presence of comorbidities, poor general condition of the patient, difficulties with bone flap storage, acute case scenarios and anatomical constraints can lead to difficulty in autografting or to the loss of the excised bone flap in a large number of cases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These cranioplasty applications have complications such as implant failure, infection, skin problems, migration of reconstruction material, sinking flap syndrome, subdural and subgaleal fluid collection, and hydrocephalus [12-18]. Studies have shown that the type of material applied does not change infection rates much, but that the increase in the number of operations increases infection rates [4, 13, 15]. Primary bone fragment replacement via single-session operation also prevents this increase in infection rates and avoids the placement of a foreign material in the skull.…”
Section: Discussionmentioning
confidence: 99%